Pauvez vous m'aider svp
Factoriser les expressions suivantes :
D=6x(2x+1)-6(3x-8)-6
E=15a²+2a⁴-5a²
F=(2x+5)(2x+5)(x+3)-7(2x+7)
G=(3x-2)(x-9)+(2x-18)


Sagot :

VINS

Réponse :

bonjour

D = que veut dire le  - 6 à la fin ?

E = a² ( 15 + 2 a² - 5  ) = a²  ( 2 a² + 10 )

F = ( 2 x + 5 ) ( x + 3 - 14 x - 49 )

  = ( 2 x + 5 ) ( - 13 x - 46 )

G = ( 3 x - 2 ) ( x - 9 ) + 2 ( x - 9 )

  = ( x - 9 ) ( 3 x - 2 + 2 )

  =  3 x ( x - 9 )

Explications étape par étape :

Réponse :

D=6(2x²+x-3x+8-1)

D=6(2x²-2x+7)

E=a²(10+2a²)

G=(3x-2)(x-9)+2(x-9)

G=(x-9)(3x-2+2)

G=3x(x-9)

Explications étape par étape :